The Development of Rimpu Culture in the Face of Modernization and Globalization (A Study Using Phenomenological Approach) - Muhammad Irfan (FiTUA: JURNAL STUDI ISLAM, 2024)
This research aims to describe the development of rimpu culture in the face of modernization and globalization in the lives of Bima people, identify the impact of the decline of rimpu culture in the midst of waves of modernization and globalization, describe the efforts of the community and government in preserving rimpu culture. This research uses qualitative research methods. This research method will describe how the views of the figures about the development of rimpu facing modernization and globalization. The type of research used is descriptive phenomenological. The source of research data consists of cultural figures, academics consisting of the head of the Dikpora office and the head of the tourism office, as well as religious leaders collecting data with qualitative research, namely observation, interviews, and documentation. The results showed that the development of rimpu culture in Bima began when Islam became the religion of the Bima people. The impact of the decline of rimpu culture is the shift in the values of the meaning of the motto maja labo dahu. Some of the things done by the government and the community to preserve rimpu culture are conducting rimpu festival activities, cultural parades, karnafal, and using rimpu in the school environment.